Tourism Capacity Development in India: The Use of ICT Enabled Mechanisms - Bhasin, Dolly (2011)
The purpose of this research is to explore if ICT mechanisms play a role in capacity building in Indian Tourism. It uses a cross disciplinary approach with ICT as well as Tourism concepts being examined. The study is divided into two parts, the first dealing with determining the main gaps in the tourism capacity in India through a situational and SWOT analysis and the second part tries to explore the role of ICT enabled mechanisms for capacity building in Indian Tourism through five representative case studies from India. Due to limited scope that can be covered in the dissertation only the ICT mechanisms related to marketing and human resource related capacity needs were examined.